A cooperação trilateral brasileira em Moçambique: um estudo de caso comparado: o ProALIMENTOS e o ProSAVANA - Fingermann, Natalia Noschese (2014)
The architecture of foreign aid is undergoing a transformation process through which the North-South divide has become increasingly blurred and trilateral cooperation, which combines opposing North-South and South-South cooperation practices, has emerged as a new type of Brazilian technical cooperation. To better understand this scenario, this thesis aims to identify and compare the motivations and practices of Brazilian trilateral cooperation agents through a comparative case study of two ongoing trilateral projects developed by the Brazilian Cooperation Agency (ABC, in the Portuguese acronym) in the agriculture sector in Mozambique: ProALIMENTOS, a partnership between the United States Agency for International Development (USAID- -Brazil) and ABC, and ProSAVANA, a partnership between Japan International Cooperation Agency (JICA) and ABC. In this light, this research draws on an actor-oriented approach to carry out a multilevel analysis that creates a link between the agent and the structure, policies and practice, with a focus on the macro, meso and micro environments. The qualitative method applied in this paper combined the observant participant and document analysis techniques, in addition to 59 semi-structured interviews, most of which were conducted during a fieldwork in Mozambique from March to June 2013. The main findings indicate that the partnership in ProALIMENTOS has led to complementary gains and transfer of know-how among the three parties, though it has facilitated overlapping of South-South cooperation practices by North-South. While the case of ProSAVANA shows no complementary gain, once there are internal and external challenges involving the Program. The lack of internal coordination and harmonization reflects on the external conflict with civil society representatives due to the communication gap between the parties, which may challenge the continuity of ProSAVANA. Finally, this research shows that Brazilian government should pay more attention to these projects of Trilateral Cooperation, once its results might impact on the credibility of Brazilian technical cooperation as a new emerging donor.